Biologi Reproduksi dan Polinasi Buatan Tumbuhan Senduduk (Melastoma malabathricum L.) - Lilis Suryani (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2017)
Abstract Melastoma malabthricum is the type with the widest area of spread compared with other species in the genus Melastoma. This research uses floral phenology observation method and pollination experiment by using bagging technique, emasculation and artificial pollination. Stigma receptivity was tested according to the Matson method. The results showed that M. malabathricum’s flowers take 14 until 21 days from bud to flower bloom. Stigma M. malabathricum is already present and receptive before anthesis flower. Fruit can be formed through self pollination (autogamy) and cross pollination (xenogamy). M. malabathricum pollination approaches the xenogamy facultative.